Evaluation of a Paradigm to Investigate Detection of Road Hazards when Using a Bioptic Telescope. Issue 9 (September 2018) - Bowers, Alex R.; Bronstad, P. Matthew; Spano, Lauren P.; Huq, Bidisha; Tang, Xiaolan; Doherty, Amy; Peli, Eli; Luo, Gang
Abstract : SIGNIFICANCE: A new driving simulator paradigm was developed and evaluated that will enable future investigations of the effects of the ring scotoma in bioptic drivers with diverse vision impairments and different telescope designs. PURPOSE: The ring scotoma may impair detection of peripheral hazards when viewing through a bioptic telescope. To investigate this question, we developed and tested a sign-reading and pedestrian-detection paradigm in a driving simulator. METHODS: Twelve normally sighted subjects with simulated acuity loss (median 20/120) used a 3.0× monocular bioptic to read 36 road signs while driving in a simulator. Thirteen of 21 pedestrian hazards appeared and ran on the road for 1 second within the ring scotoma while participants were reading signs through the bioptic. Head movements were analyzed to determine whether the pedestrian appeared before or only while using the bioptic. Six subjects viewed binocularly, and six viewed monocularly (fellow eye patched). Two patients with real visual acuity loss in one eye and no light perception in the other performed the same tasks using their own telescopes. RESULTS: For the monocular simulated acuity loss group, detection rates were significantly higher when the pedestrian appeared before using the bioptic than when it appeared while using the bioptic and was likely within the area of the ring scotoma (77% vs. 28%, P < .001). For the binocular simulated acuity loss group, there was no significant difference in detection rates for pedestrians that appeared before or while using the bioptic (80% vs. 91%, P = .20). The two monocular patients detected only 17% of pedestrians that appeared while looking through the bioptic. CONCLUSIONS: Our results confirm the utility of the testing paradigm and suggest that the fellow eye of normally sighted observers with simulated acuity loss was able to compensate for the ring scotoma when using a monocular bioptic telescope in a realistic driving task.